2019
DOI: 10.1002/jts.22455
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Patterns of Polyvictimization and Their Associations with Posttraumatic Stress Disorder and Complex Posttraumatic Stress Disorder in the Israeli Population

Abstract: Although evidence is accumulating for the conceptual validity of the ICD-11 proposal for posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD), our understanding of the specificity of trauma-related predictors is still evolving. Specifically, studies utilizing advanced statistical methods to model the association between trauma exposure and ICD-11 proposals of traumatic stress and differences in profiles of trauma exposure are lacking. Additionally, time since trauma and a clear memory of the trauma ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…The present results allow for a more comprehensive exploration of how PTEs across the life course may relate to differential alcohol use outcomes. The findings are consistent with research on multiple trauma types in that interpersonal PTEs (e.g., IPV) appeared to be related to more adverse outcomes (Vang et al., 2019), in this case, problematic alcohol use, compared to situational PTEs (e.g., combat exposure, natural disasters). The profiles characterized in these analyses offer a clearer picture of potential clinical relevance and interpretability than in prior work, indicating clear clustering of PTEs across defined exposure types and relevance to risky and potentially clinically significant alcohol use.…”
Section: Discussionsupporting
confidence: 89%
“…The present results allow for a more comprehensive exploration of how PTEs across the life course may relate to differential alcohol use outcomes. The findings are consistent with research on multiple trauma types in that interpersonal PTEs (e.g., IPV) appeared to be related to more adverse outcomes (Vang et al., 2019), in this case, problematic alcohol use, compared to situational PTEs (e.g., combat exposure, natural disasters). The profiles characterized in these analyses offer a clearer picture of potential clinical relevance and interpretability than in prior work, indicating clear clustering of PTEs across defined exposure types and relevance to risky and potentially clinically significant alcohol use.…”
Section: Discussionsupporting
confidence: 89%
“…This additional trauma exposure after escape was also associated with current CPTSD symptoms, which is consistent with a recent report indicating that childhood abuse histories are related to further revictimization and that PTSD symptoms of revictimization are associated with childhood abuse (Gama et al, 2021 ). This is also supported by Vang et al ( 2019 ), who reported that being poly-victimized with both childhood and adulthood interpersonal trauma increases the risk for CPTSD.…”
Section: Discussionsupporting
confidence: 65%
“…Future research should include CSA survivors with psychopathology to reveal which aspects during the perinatal period may be associated with prolonged distress in clinical populations. Investigating confounding variables, such as multiple child maltreatment exposures 43,44 should also be addressed in future research. Finally, researchers must be mindful of the researcher-participant relationship to prevent (re)traumatization when studying this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%